A value-centric business model framework for managing open data applications. Issue 1 (2nd April 2016) - Yu, Chien-Chih
ABSTRACT: Open data has been noted as one of the main objectives of open government, and eventually as a foundation for creating value-added business and public applications in various domains such as e-Tourism and e-Participation. Value proposition to and creation for all stakeholders in the open data service chain are key factors to the success of developing and delivering Open Data Applications (ODAs). As critical is the design and development of suitable business models that help direct value proposition, creation, and assessment, and further sustain continuous business operations. In the literature, there is still a lack of studies comprehensively addressing issues regarding value creation and business model design of open data applications. This article introduces an ODA applicable value-centric Business Model (ODA-vBM) framework for guiding the development of operational business models that support the full value management process, including value identification, proposition, creation, and assessment. Major components of the new value-centric business model framework include value and objectives, actors and roles, services and systems, resources and costs, functions and activities, as well as actions and performances. The ODA-vBM framework can be used by government and other organizations involved in the ODA service chain to direct the construction and evaluation of business models for matching individual conditions and needs. Also proposed in this article is an integrated design science research and action research approach for effectively building and evaluating the business model framework, as well as operational business models in specific organizational contexts. Cases with diverse application domains, project levels, and service chain structures are presented to show the feasibility and usefulness of the introduced business model framework, as well as the derived organization-specific business models for open data applications.